The use of MRS in the evaluation of pediatric epilepsy - Caruso, Paul A.; Johnson, Jason; Thibert, Ron; Rapalino, Otto; Rincon, Sandra; Ratai, Eva-Maria (Journal of Pediatric Epilepsy, 2013)
This chapter is a practical “why, how to, and when” chapter, written in three parts to address three questions that arise when the epileptologist or neuroimager evaluates a patient with epilepsy. Why do magnetic resonance spectroscopy (MRS)? How to do MRS in the patient with epilepsy? When, that is, in what clinical-imaging setting, can MRS help to diagnose or manage the patient with epilepsy?
Keywords: MRI; MRS; epilepsy; inborn error of metabolism; malformation of cortical development; focal cortical dysplasia; tumor; neoplasm